Response suppression by visual stimuli paired with postsession d-amphetamine injections in the pigeon. - Glowa, J R (1983)
Responding of pigeons, maintained under a fixed-interval 3-minute schedule of food presentation, was decreased on days that the color of the lights illuminating the food magazine was changed and d-amphetamine (1.0 mg/kg, i.m.) was injected after the session. Responding was not decreased by keylight color changes paired with postsession d-amphetamine or by postsession injections of saline. Administration of pentobarbital (3.0 to 5.6 mg/kg), but not d-amphetamine (.3 to 3.0 mg/kg), before the session increased rates of responding suppressed by drug-paired magazine lights. Responding maintained under a fixed-ratio 30-response schedule was not decreased when differently colored magazine lights were paired with a low (.3 mg/kg) postsession dose of d-amphetamine; with high (3.0 mg/kg) postsession doses, however, responding was completely suppressed after two pairings. The effects of pairing magazine stimuli with an intermediate (1.0 mg/kg) postsession dose of d-amphetamine depended upon the magnitude of prior postsession doses. After being paired with a low dose, stimuli paired with 1.0 mg/kg did not suppress responding. After being paired with a high dose, stimuli paired with 1.0 mg/kg completely suppressed responding. The suppression of food-maintained responding by stimuli paired with postsession drug administration depends upon both behavioral and pharmacological variables.